Exploring Neurodegenerative Diseases: Bridging the Gap between in vitro and in vivo Models - El Elhaj, Abubaker; Onger, Mehmet Emin (Current Pharmaceutical Design, 2026)
Neurological disorders are brain conditions characterized by the loss of nerve cells, leading to a decline in function. Standard examples include dementia, tremors, involuntary movements, muscle weakness, and autoimmune attacks. The most common form of dementia is Alzheimer's, affecting over 5 million elderly individuals, while tremors, stiffness, and slow movement are caused by Parkinson's. Involuntary movements and emotional problems are caused by Huntington's, while muscle weakness and eventual demise are caused by Amyotrophic lateral sclerosis. Vision problems, fatigue, and difficulty walking are caused by Multiple sclerosis (MS), an autoimmune disease that attacks the myelin sheath. In vitro models provide cost and complexity reduction, environmental control, and high-throughput. Researchers employ both cell-based (in vitro) and animal-based (in vivo) models to investigate neurodegenerative illnesses and endeavor to formulate novel treatments for diverse conditions. In vitro models provide cost and complexity reduction, environment control, and high-throughput screening of potential therapeutic agents compared to in vivo models. Nevertheless, they possess constraints, including the absence of intricate interactions that transpire in the entire organism and the inability to reproduce the disease progression completely.
Keywords: immunological disorders